The Effect of Green Governance on Organizational Performance Moderated by Tax Administration Reform - Bandiyono, Agus; Murwaningsari, Etty; Augustine, Yvonne (Dinasti Publisher, 2022)
The purpose of this research to describe the effect of the implementation of green governance on organizational performance and to determine whether the tax administration system renewal can strengthen the application of green governance on organizational performance.Methodology-The population of this research is the employees of the tax office throughout Indonesia. The sample of this research is senior employees, employees who have echelon IV positions and at least have the position of section head.Research Findings-This research resulted in a conclusion, namely the application of green governance results in better organizational performance. Tax administration system renewal resulted in decreased organizational performance. Tax administration system renewal can increase influence of green governance on organizational performance for the better.Theoretical contribution/Originality: Researchers add a new dimension to the green governance variables, namely participation and law enforcement.